Técnicas de tradução e a abordagem integrada: uma proposta de formação presencial e online para tradutores português-inglês - Camargo, João Lucas Cavalheiro (2020)
The discipline of Translation Studies rises relatively early in 1972 with James S. Holmes’ publication. One of the fields of research aims the education of translators. According to Venuti (2018), many translation courses exist, but no courses based on an interpretative model were created. Venuti (2019) reinforces that is necessary to create teaching elements towards a hermeneutic translation. Costa (2018) describes that in the Brazilian context, it is necessary to use technologies in the process of learning and teaching, it is also necessary to investigate distance learning in translator education, and that it is relevant to have social responsibility, both in practice and translator teaching. Therefore, the following questions are asked: how is it possible to design, implement and assess an online and an in-person course in the light of hermeneutic translation and what are the methodological and pedagogical underlying to these practices? Grounded on a descriptivist theoretical framework, based on an interpretative and hermeneutic view of the translation process, associated with linguistic theories of translation about equivalence, theorizing, text scopes and translation techniques/strategies, it aims to answer the aforementioned questions. Of qualitative nature, this investigation relies on the validation of specialist professors of the initial syllabus and on data collection with instruments and views inspired by (n)etnographic approaches. It analyses data with its own theoretical framework of translation, of a hermeneutic view to respond the research questions and interpret data. This research established the documentation and creation, design, implementation and analysis process of creating translation courses, in online and in-person contexts towards the development of hermeneutic translation framework elements suggested in this investigation.